Ammonianitrogen removal by chlorella sp. in different landfill leach dilutions - Celia Cavalcante de Paula e Silva, Maria; Virginia de Conceição Albuquerque, Maria; Milena Moura Rodrigues, Roberta; de Oliveira Ramos, Railson; Morgana Ferreira Costa, Evelyne; Silva Lopes, Wilton; William Pearson, Howard; Duarte Leite, Valderi (Seven Editora, 2023)
Sanitary landfill leachate is a highly polluting complex matrix wastewater. It has high concentrations of ammoniacal nitrogen, phosphorus, carbonaceous matter and recalcitrant substances. The application of microalgae to remove pollutants from leachate has been investigated. The Chlorella sp. applied in this work, was isolated from the leachate from the sanitary landfill in João Pessoa-PB. The experimental system consisted of 3 bioreactors with a useful volume of 210 mL, being 200 mL of leachate diluted in distilled water and 10 mL of Chlorella sp. in stationary phase, fed in batch, photoperiod of 24 hours, temperature of 27o C, TDH of 240 hours and influent concentrations of ammoniacal-N of 46, 192 and 575 mg. L-1 and the positive control. The highest cell densities were recorded at the influential ammonia N concentrations of 46 and 192 mg. L-1, with increments greater than 250% until the 5th day of monitoring. The lowest growth was obtained at the ammoniacal nitrogen concentration of 575 mg. L-1 with 12% increments until the 5th day. The analysis of the residual nitrogen mass calculation in the system indicated mass removal of 66, 59 and 56% for affluent inputs of 9.66; 40.32 and 120.75 mg-N for respective influent-N concentrations of 46, 192 and 575 mg. L-1. The results are indicative that Chlorella sp. can adapt and grow in different concentrations of ammoniacal nitrogen, having the potential to be applied efficiently in the tertiary treatment of landfill leachate. DOI: https://doi.org/10.56238/methofocusinterv1-120